2007
DOI: 10.1038/sj.onc.1210933
|View full text |Cite
|
Sign up to set email alerts
|

Differential motility of p190bcr-abl- and p210bcr-abl-expressing cells: respective roles of Vav and Bcr-Abl GEFs

Abstract: The chimeric oncogene Bcr-Abl is known to induce autonomous motility of leukemic cells. We show here that p210

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 27 publications
4
29
0
Order By: Relevance
“…Results are obtained by counting the number of migrating cells in the ECM gel [163]. Several authors have used the transwell chamber assay in 3D matrix for testing invasion ability of leukemia cells [164,165]. This method was later refined, by observing leukemia cell motility in 3D Transwell with time-lapse microscopy.…”
Section: D Leukemia Models For Testing Motility/ Invasionmentioning
confidence: 99%
“…Results are obtained by counting the number of migrating cells in the ECM gel [163]. Several authors have used the transwell chamber assay in 3D matrix for testing invasion ability of leukemia cells [164,165]. This method was later refined, by observing leukemia cell motility in 3D Transwell with time-lapse microscopy.…”
Section: D Leukemia Models For Testing Motility/ Invasionmentioning
confidence: 99%
“…The GTPase-dependent actin regulatory pathway has been described mostly to affect BCR-ABL p210 -driven leukemogenesis, which, in contrast to , comprises the Bcr guanine exchange domain (Tala et al, 2013). It has been shown that RAC1 deficiency depletes BCR-ABL p210 progenitors (Sengupta et al, 2010), and that the RAC1 and CDC42 exchange factor VAV drives leukemogenic proliferation and survival (Chang et al, 2012), as well as motility (Daubon et al, 2008). These studies and our findings suggest that coupling of small GTPase signals to actin polarization, which is required for directed migration may be a target to reduce leukemogenesis or to prevent reengraftment of leukemia after therapy, not only as has been suggested for BCR-ABL p210 (Thomas et al, 2007) but also for BCR-ABL p185 .…”
Section: Discussionmentioning
confidence: 99%
“…guanine nucleotide exchange factor (GEF) activity in hematopoietic BaF3 cells (Harnois et al, 2003;Daubon et al, 2008). However, RhoA activity was almost undetectable in BM-derived Ph( þ ) primary cells (data not shown).…”
Section: Figure 6 the Involvement Of Vav1 In P210mentioning
confidence: 99%
“…BcrÀAbl for Rac1 stimulation (Bassermann et al, 2002;Daubon et al, 2008). In addition, phosphorylation and activation of Vav1, induced by SDF-1a, controls the chemotactic response in human primary lymphocytes (Vicente-Manzanares et al, 2005).…”
Section: Vav1 Mediates P210mentioning
confidence: 99%
See 1 more Smart Citation